TEACHING ENGLISH LITERATURE IN EFL CLASSROOM AS THE STRENGHTENING OF LANGUAGE USE : FROM ANCIENT PEDAGOGY TO MODERN ACADEMY - Oktariza, Dodi (Universitas Muara Bungo, 2024)
The paper discussed about teaching of English in EFL classroom seen generally as a regular activity as well as teaching of English literature as a rich source of authentic material of English language teaching itself and the strengthening of English language use. For many years, English literature has been taught at a secondary or tertiary level even at University level. However, teaching English literature has not been given yet much emphasis on an appropriate methodology of teaching due to it is still considered as one of the most difficult subjects to teach.Generally, there are two terms of methodology that mostly discussed by experts, namely ancient/traditional pedagogy and modern academy. Learning about traditional, it has its roots in the ancient pedagogy of classical language instruction. The points are students only mimicking and parroting their teachers knowledge. In fact, such pedagogy was being successful in beginning Latin and Greek classes. In contrary, we do not intend to suggest that students learn only from their teachers, who transmit their knowledge and understanding freely, but what do we mean that pedagogy frames course content and different frames invite different kinds of understanding of content and that parts of modern academy. At last, central to teaching literature in the classroom is giving the students’ right to be involved freely in their experiences and let them observed literary as part of their life more closely.